Measure of Non-Compactness in The Study of Solutions for A System of Integral Equations - Vatan Karakaya; Mohammad Mursaleen; Nour El Houda Bouzara; Derya Sekman (IndoMS, 2019)
In this work, we prove the existence of solutions for a tripled systemof integral equations using some new results of fixed point theory associated withmeasure of noncompactness. These results extend the results in some previousworks. Also, the condition under which the operator admits fixed points is moregeneral than the others in literature.